Microwave Pre-processing Effect on Pectin Yield from Citrus Raw Material - Alekseev, Gennady; Egorova, Olga; Egorov, Aleksey (KnE Life Sciences, 2020)
The article describes a more environmentally friendly method to produce pectin compared to the classical acid scheme, which requires the use of strong mineral acids and toxic solvents. This method of obtaining pectin, like other analogs of the classical method, causes a decrease in the yield of the final product. This study aims to find ways of eliminating these barriers and increase the yield of pectin. The paper investigates the possibility to increase the yield of pectin obtained by acid hydrolysis applying citric acid through the use of preliminary microwave exposure to citrus raw materials. The work compares pectin quality indicators, such as the degree of esterification, molecular weight and gelation, for raw materials dried by the convective method and the combined method consisting of microwave pretreatment and blowing dry air. Curves of comparable pre-drying methods are presented. The rate of pectin yield at the stages of hydrolysis depending on the drying methods is analyzed. Optimal power modes for preliminary microwave drying of citrus raw materials are selected. The data obtained are valuable for both development and improvement of industrial technology of pectin production using environmental methods of extraction without the use of strong mineral acids to increase the yield and quality of pectin.